Knowledge and perceptions of the roles of anesthesiologists as providers of healthcare services: toward better-educated patients - Anwar Zahran; Firas Besharieh; Yazan Hamdan; Taysir Alsadder; Mohammad Jaber; Ramzi Shawahna (BMC Health Services Research)
Abstract Background In modern healthcare systems, the scope of practice for anesthesiologists is expanding within and beyond the traditional perioperative care continuum. This study was conducted to assess the knowledge and perceptions of perioperative patients of the roles of anesthesiologists as providers of healthcare services in different Palestinian hospitals. The study also assessed associations between the patients' different demographic and clinical variables and their knowledge and perceptions about the roles of anesthesiologists. Method This study was conducted using a cross-sectional design and a questionnaire among perioperative patients admitted for elective surgeries in five major public and private hospitals in the Nablus, Tulkarm, Jenin, and Salfit governorates of the West Bank of Palestine. The data were collected between September 2023 and December 2023. Results Of the 500 patients invited, 411 patients completed the questionnaire, giving a response rate of 82.2%. The overall knowledge score of the patients about the roles of anesthesiologists was 59.4% (18.8%). The majority of the patients lacked awareness about the roles of anesthesiologists outside the operating room. There was a low positive correlation between the self-rated general health and overall knowledge score (Pearson's r = 0.17, p-value < 0.001). Similarly, knowledge scores were significantly higher for the patients who had a university education (p-value =  < 0.001) and had a degree in one of the medical/health fields (p-value =  < 0.001). On the other hand, the patients who lived in refugee camps (p-value = 0.048), had a blue-collar job (p-value = 0.005), and were scheduled to receive orthopedic surgeries (p-value = 0.035) had significantly lower knowledge scores. Conclusion The findings of this study showed that perioperative patients in Palestine had inadequate knowledge about anesthesia and the roles of anesthesiologists, especially outside the operating room. Efforts should be made to improve the knowledge and perception of perioperative patients about anesthesia and the roles of anesthesiologists as providers of healthcare services. These efforts should be tailored to target uneducated patients, who have blue-collar jobs, live in refugee camps, and are scheduled to receive orthopedic surgeries.